Experimental design for laboratory biologists maximising information and improving reproducibility - Lazic, Stanley E. (Cambridge University Press, 2016)
An ideal resource for anyone conducting lab-based biomedical research, this guide shows how to design reproducible experiments that have low bias, high precision and widely applicable results. It explores key ideas in experimental design, including reproducibility and replication, assesses common designs, and shows how to plan for success.